Intervensi Koroner Perkutan Primer untuk Infark Miokard Elevasi ST di Pusat Jantung Pemula di Indonesia: 100 pasien pertama - Yahya Juwana; Jan Paul Ottervanger; Jan-Henk Dambrink; Arnoud van’t Hof; Menko-Jan de Boer; Jan Hoorntje; Harry Suryapranata (Jurnal Kardiologi Indonesia, 2011)
Background: The benefits of Primary percutaneous coronary intervention (PCI) for ST elevation myocardial infarction (STEMI) have been demon-strated, but most studies were conducted in experienced centres in western world. Experience, logistics and patient characteristics may differ in other parts of the world, particularly in a starting center.Methods: Data on all consecutive STEMI patients treated with primary PCI in Cinere hospital, Jakarta, Indonesia were collected in a prospective database.Results:,Between July 2006 and December 2008, a total of 100 patients with STEMI were treated by primary PCI. Mean age was 56.9 ±10.4 years (range 37-82), 88% was male. Mean time between onset of chest pain and admission was 369 ± 388 minutes. The mean time between admission and balloon inflation was 258 minutes. Before PCI, 50% of patients had TIMI 0 flow. After primary PCI 94% of patients had TIMI 2/3 flow. There were no deaths in the catheterisation room, and no emergency coronary bypass surgery was needed as a result of PCI complications. Mean left ventricular ejection fraction as measured by echocardiography after 1 day was 48 ± 12 %.Conclusions: Outcome after primary PCI at a starting center is excellent in this series. Primary PCI was effective in restoration of TIMI flow, without complications. Time delay between symptom onset, admission and balloon inflation was long and all efforts should be encouraged to shorten this.